SOCIAL MEDIA MARKETING AND BRAND EQUITY IN THE HOSPITALITY INDUSTRY: EVIDENCE FROM IMO STATE, NIGERIA (UNIZIK Journal of Marketing, 2025)
This study investigated the effect of social media marketing strategies on brand equity within thehospitality industry in Imo State, Nigeria. In the face of increasing digitalization and changingconsumer behavior, hospitality businesses are turning to social media as a vital tool for brandpositioning and customer engagement. The study operationalised social media marketing usingfive key constructs: content quality, interactivity, platform diversity, user-generated content(UGC), and engagement metrics. These constructs were investigated within the framework ofKeller’s Customer-Based Brand Equity Model, Social Exchange Theory, and Social NetworkTheory, which collectively underscore the psychological and relational mechanismsunderpinning brand development in the digital space. A quantitative research design wasadopted, involving the development, validation and administration of a structured questionnairetitled “Social Media Marketing and Brand Equity Questionnaire” to 260 hospitality consumersacross hotels and related service firms in Imo State. The reliability of the instrument wasassessed using Cronbach’s alpha coefficient, yielding a reliability index of 0.85, indicating a highlevel of internal consistency. Data were analysed using multiple regression and StructuralEquation Modeling (SEM) techniques. The findings reveal that all five constructs significantlyinfluence brand equity, with user-generated content and content quality emerging as the mostimpactful variables. The study offers both theoretical and practical contributions: it deepens theunderstanding of social media’s role in brand equity formation in emerging economies, and itprovides actionable insights for hospitality marketers seeking to strengthen brand-customerrelationships in competitive digital environments.
Keywords: social media marketing, brand equity, hospitality, Nigeria, user-generated content, platform diversity, Keller’s model